Contemporary Strategies and Barriers to Transplantation Tolerance. Issue 8 (August 2018) - Ezekian, Brian; Schroder, Paul M.; Freischlag, Kyle; Yoon, Janghoon; Kwun, Jean; Knechtle, Stuart J.
Abstract : Abstract: The purpose of this review is to discuss immunologic tolerance as it applies to solid organ transplantation and to identify barriers that hinder the achievement of this long-term goal. First, the definition of tolerance and an introduction of mechanisms by which tolerance exists or can be achieved will be discussed. Next, a review of contemporary attempts at achieving transplant tolerance will be described. Finally, a discussion of the humoral barriers to transplantation tolerance and potential ways to overcome these barriers will be presented. Abstract : In this review regarding tolerance induction in organ transplantation, the authors highlight the current attempts of induction with their mechanisms, the contemporary barriers and the specific role of humoral immunity